EUPHEMISM USED BY DONALD TRUMP AND HILLARY CLINTON IN THE 2016 POLITICAL DEBATE - Roaini Shaunaa; Nurul Chojimah; Eni Sugiharyanti (Journey: Journal of English Language and Pedagogy, 2022)
This study aimed to investigate the types and functions of euphemism expressions used by Donald Trump and Hillary Clinton in a political debate text, and also to reveal the differences between men and women in the use of euphemisms under the theory of language and gender. This study used descriptive qualitative. The data of this study were the words, phrases, clauses, and sentences uttered by Donald Trump and Hillary Clinton in a political debate and were collected by transcription technique. The data then were analyzed in the form of euphemism guided by Warren's (1992) model of euphemism and the functions of euphemism by the theory of Ryabova (2013). The result found 25 data of euphemisms. There were 10 euphemism expressions used by Donald Trump and 15 euphemism expressions used by Hillary Clinton. The result showed that women used euphemistic expressions more frequently than men because women prefer to be more polite and less direct directives than men.